KOAGULYANT-ADSORBENTTIŃ ADSORBCIYALÍQ QÁSIYETIN KOLORIMETRIYALÍQ USÍL MENEN ÚYRENIW - Aymurzaeva, L.G.; Aytbaeva, H.B.; Qutlimuratova, Sh.A. (SCIENCE and SOCIETY, 2025)
This article presents the adsorption properties of thermally activated coagulants-adsorbents, the structural-sorption indicators of coagulants-adsorbents, and the pore volume, as well as their dependence on adsorption.